Evaluación de la remoción foto-catalítica de metano (ch4) sobre películas de dióxido de titanio modificadas con nanopartículas de plata bajo luz visible (2020)
The present work has as main objective, to evaluate the photocatalytic removal of methane on modified TiO2 films with low silver nanoparticles visible light; natural gas (methane) removal was performed under visible light and ultraviolet in order to evaluate the versatility of modified TiO2 catalyst with silver nanoparticles. The titanium dioxide suspension was deposited by two methods, doctor blade and spin coating; the films obtained were modified by the dip method coating, where 4 methods were used to obtain the silver nanoparticles A follow-up was conducted to examine the operation of modified films; for this, methylene blue was used, resulting in a 75% methylene blue removal percentage under visible light; in addition to that a silver particle size was obtained by below 100 nm approximately 35 to 40 nm.